Neoliberal labyrinth: Epistemic freedom and knowledge production in higher education in the Global South - Sibonokuhle Ndlovu; Emnet T. Woldegiorgis (Transformation in Higher Education)
In the 21st century, knowledge has become the driving force behind societal progress, emphasising the need for higher education to produce contextually relevant knowledge that addresses the multifaceted challenges faced by local communities. It is in this respect that knowledge needs to be generated through one’s position of epistemic location in higher education. However, academics positioned at the pinnacle of knowledge production in higher education find themselves entangled in a global crossroads. On the one hand, they are expected to exercise epistemic freedom by producing knowledge from their centralities and unique positionalities. On the other hand, they are constrained by the pervasive influence of neoliberalism, a paradigm that dictates that knowledge production should be subservient to market dynamics. To interrogate the intricacies of the impediments placed on academics seeking to exercise their epistemic freedom, this article utilises a desktop literature review, underscored by the theoretical framework of Decolonial Theory. The examination elucidates how these constraints hinder the production of knowledge from the centrality of the Global South. The article draws examples from South African higher education as a point of reference, providing examples that underscore the global challenges of neoliberal policies in higher education. Central to the thesis advanced in this article is the contention that, within the existing neoliberal framework of higher education driven by market forces and productivity imperatives, the production of knowledge from the position of one’s centrality is limited and the ability to produce locally relevant knowledge is fundamentally restricted. Consequently, the epistemic freedom of academics within higher education across the Global South is imperilled.